Sonic branding: how sonic logo contour affect consumers' perceived brand personality and brand recall - Ryani, Nabela Huwaida (2021)
Sonic branding strategy is commonly used by brands to show and communicate their values and identity in parallel with other sensory branding strategy. Sonic logos are important part of sonic branding. Being one of the key elements of sonic branding, it is essential to explore how different feature consist in sonic logos affect consumers’ behavior. This study aimed to investigate how different sonic logo contour influences consumers’ perspective towards brand personality and how it affects their brand recall. This study used brand personality scale developed by Aaker (1997) consisting of five brand personality dimensions (Sincerity, Excitement, Competence, Ruggedness, Sophistication). Sonic logo features were controlled and manipulated resulting in three different versions of sonic logo contour (Ascending, Descending and Constant) with three non-existing brands and placed in eleven seconds dummy podcast show. The result shows that each brand personality dimension was associated with different sonic logo contour with dimension Sincerity and Competence associated with the Ascending sonic logo, dimension Excitement associated with the Constant sonic logo, and dimension Ruggedness associated with Descending sonic logo contour. Furthermore, Brand recall study showed that dimension Sincerity and Competence positively influence brand recall based on consumers’ self-evaluation for the hypothetical brand. Further investigation should try to better understand the process of how different sound features affect different consumers’ behavior in relation to branding theory for marketing implications.